A novel technique for large lateral enterocutaneous fistula management after intestinal transplantation. (30th July 2021) - Oliva, Agustina R; Violo Gonzalez, Paula; Lerendegui, Luciana; Sanchez Clariá, Rodrigo; Moldes, Juan; Lobos, Pablo
Abstract: Background: Enterocutaneous fistula (ECF) is a serious and complex problem when affecting children, being responsible for a high morbidity burden, with an estimated mortality rate of 10 to 20%. There are many therapeutic options, including surgery and a wide variety of nonoperative strategies. Prognosis of ECF closure depends on the output and also on the patency of distal bowel. Spontaneous closure without operative intervention occurs in approximately 50% of patients with lateral ECF and distal bowel transit, but this drastically decreases in high output fistulas. High‐volume fistula output and consequent skin damage are a great challenge for the health‐care team. Methods: We describe a postoperative complication that required a new nonoperative technique for the transient management of a lateral high‐output ECF, involving the insertion of an occlusive device in order to redirect intestinal content to the distal bowel, reducing the fistula output. Results and conclusions: The main benefit of this nonoperative technique is the ability to occlude a high‐output fistula, allowing the distal flow to be restored and reducing abdominal wall damage, as a bridge to definitive surgical closure.